A POCl3-mediated synthesis of substituted fused azoacridones derivatives1. Issue 36 (23rd April 2015) - Li, Xi; Gao, Chunmei; Yang, Ti; Zhang, Bin; Tan, Chunyan; Liu, Hongxia; Jiang, Yuyang
<x xml:space="preserve">Abstract</x> We provide an efficient approach to synthesize fused azoacridone derivatives, which showed broad substrate scope and good yields.